A função discursiva dos pareceres descritivos na comunicação dos resultados de avaliação: um estudo do gênero em uma perspectiva textual-discursiva - Mengue, Bárbara Vier (Universidade do Vale do Rio dos Sinos, 2019)
The object of study of this dissertation are questions built on the function that the descriptive opinions play in the expression of results of Basic Education students. The research analyzes seven written opinions for Elementary and High School students from a private school in the Vale dos Sinos region. The general objective is to verify the linguistic-discursive function of the descriptive opinions in the communication of the students' evaluation results. For that, the communication situation in which the opinions are inserted, and the linguistic-discursive marks are analyzed in the way the speaker perceives its interlocutor, considering the restrictions imposed by the communication situation, as well as the effects of sense that these marks can exercise in their interlocutors. We use the Semiolinguistics postulates, of Charaudeau (2016), and the Textual Analysis of Discourses, of Adam (2011). Charaudeau analyzes the discourse in three levels, which correspond to the competences of the subject: the situational level, the discursive level and the semiolinguistic level. Our study unfolds at those three levels for the analysis of opinions. At the semiolinguistic level, we incorporate the theory of Textual Analysis of Discourses, using the categories of modalization and acts of discourse. The contractual relations determine, in part, the linguistic choices. In staging the act of communication, the speaker’s relationship of influence is established on the interlocutor, in an allocutionary behavior. The teacher establishes, with his statement, a status of superiority, mobilizing and organizing categories of the language to account for this position, such as Judgment, Injunction, Suggestion and Interpellation. It is worth noting the constant use of deontic modalizers, markers of the injunction, which may be related to the discursive purpose of the genre: know-how (informing) with a view to do-how (act). The analyzed opinions present a similar structure, in which the use of the Descriptive way of organizing the discourse predominates. The use of descriptive organization procedures for naming, locating-situating and qualifying was observed. Through these procedures, there is a subjective construction of the world in the opinion. It is concluded that the linguistic-discursive function of the descriptive opinions goes far beyond informing. They aim to influence the interlocutor, leading him/her to act. Opinions are written for the students and, in the elementary school, also for the parents/guardians. Opinions can serve as a safeguard to the school and the teacher, in the case of a student’s failure. They are important documents for expressing the evaluation results, can favor a mediating evaluation or reinforce a classification evaluation. The aspects highlighted from the analyzes carried out can help the educational institutions to reflect on the way they elaborate their opinions, verifying if they are in fact coherent with the pedagogical proposal of the school and based on current concepts of evaluation, teaching and learning.
Keywords: Gênero discursivo; Parecer descritivo; Semiolinguística; Avaliação; Discursive genre; Descriptive opinion; Semiolinguistic; Evaluation; ACCNPQ::Lingüística, Letras e Artes::Lingüística